Analisis Kendala Guru TK Dalam Penyusunan Instrumen Penilaian Di Banda Aceh Dan Aceh Besar - Siti Ulviani; Lina Amelia; Siti Jaza Ul Aufa; Chairunnisa; Tasya Hindriani; Zakiatul Ulya; Maya Rosita Urza (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Assessment instruments play a crucial role in helping teachers understand the holistic development of early childhood, including cognitive, social-emotional, language, and motor aspects. However, many kindergarten teachers still encounter difficulties in developing and applying appropriate assessment instruments that align with children’s characteristics and curriculum demands. This study aims to analyze the challenges faced by kindergarten teachers in Banda Aceh and Aceh Besar in designing assessment instruments for early childhood development. The research employed a qualitative descriptive approach involving fifteen kindergarten teachers selected through purposive sampling. Data were collected using semi-open questionnaires and analyzed thematically following the model of Miles, Huberman, and Saldaña. The findings reveal that teachers possess a strong awareness of the importance of authentic assessment but face major challenges such as limited time, difficulties in formulating developmental indicators, and low digital literacy. Teachers attempt to overcome these constraints through peer collaboration and express the need for continuous training and practical guidelines from educational institutions. The study concludes that kindergarten teachers require systematic support to enhance their assessment competence so that authentic, objective, and development-oriented evaluation can be implemented effectively. The novelty of this study lies in mapping the real challenges faced by kindergarten teachers in Aceh within the context of the Merdeka Curriculum implementation, serving as a foundation for strengthening teacher capacity in authentic assessment.